2005
DOI: 10.4071/1551-4897-2.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of anisotropic conductive joints for bumpless flip-chip on flex packages under thermal stresses

Abstract: The reliability of ACF (Anisotropic conductive film) interconnection is a serious concern especially under thermal loading condition. This paper focuses on the online contact resistance behavior of the ACF joint for bumpless flip-chip on flex packages during different thermal cycling conditions. In this work, flip chips of 11×3 mm2 having bare aluminum pad were used. Real time contact resistance (i.e. live measurement contact resistance variation with temperature) was measured by four points probe method when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This is because the thermomechanical stresses due to differences in the coefficient of thermal expansion (CTE) increase the further the joints are located from the centre of the chip. Earlier studies have shown that ACF failures occur more often around corner joints than in the joints situated in the middle of a chip [8] [11]. The reliability of the DCs can be observed to increase with the higher bonding forces.…”
Section: Resultsmentioning
confidence: 89%
“…This is because the thermomechanical stresses due to differences in the coefficient of thermal expansion (CTE) increase the further the joints are located from the centre of the chip. Earlier studies have shown that ACF failures occur more often around corner joints than in the joints situated in the middle of a chip [8] [11]. The reliability of the DCs can be observed to increase with the higher bonding forces.…”
Section: Resultsmentioning
confidence: 89%